2007
DOI: 10.1152/ajpendo.00572.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of insulin sensitivity, β-cell function, and β-cell mass during the development of diabetes in fa/fa rats

Abstract: Both male Zucker Fatty (mZF) and lower-fat-fed female Zucker diabetic fatty (LF-fZDF) rats are obese but remain normoglycemic. Male ZDF (mZDF) and high-fat-fed female ZDF rats (HF-fZDF) are also obese but develop diabetes between 7 and 10 wk of age. Although these models have been well studied, the mechanisms governing the adaptations to obesity in the normoglycemic animals, and the failure of adaptation in the animals that develop diabetes, remain unclear. Here we use quantitative morphometry and our recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
7
47
0
Order By: Relevance
“…Hence, pharmacological inhibition of renal glucose reabsorption effectively reduces hyperglycemia with preserved b-cell secretory function and b-cell mass, which strongly suggests that improving glycemic control independent of insulin secretion may lead to b-cell sparing effects of empagliflozin. This interpretation is in good agreement with the hypothesis that glucolipotoxicity and progressive b-cell exhaustion caused by continued increased insulin demand, in combination, may lead to disease progression as a consequence of islet b-cell secretory defects, lowered b-cell proliferative rate, and augmented apoptotic b-cell death (Pick et al, 1998;Prentki and Nolan 2006;Topp et al, 2007;Paulsen et al, 2010). Correspondingly, the present study indicated that vehicletreated ZDF rats exhibited a significantly lower total islet and absolute b-cell mass with a concomitant significant reduction in the number of Ki-67-positive proliferating b cells as compared with baseline levels.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, pharmacological inhibition of renal glucose reabsorption effectively reduces hyperglycemia with preserved b-cell secretory function and b-cell mass, which strongly suggests that improving glycemic control independent of insulin secretion may lead to b-cell sparing effects of empagliflozin. This interpretation is in good agreement with the hypothesis that glucolipotoxicity and progressive b-cell exhaustion caused by continued increased insulin demand, in combination, may lead to disease progression as a consequence of islet b-cell secretory defects, lowered b-cell proliferative rate, and augmented apoptotic b-cell death (Pick et al, 1998;Prentki and Nolan 2006;Topp et al, 2007;Paulsen et al, 2010). Correspondingly, the present study indicated that vehicletreated ZDF rats exhibited a significantly lower total islet and absolute b-cell mass with a concomitant significant reduction in the number of Ki-67-positive proliferating b cells as compared with baseline levels.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, as the β-cell mass increases to compensate for greater whole-body insulin demand, the feedback system is maintained by increasing β-cell turnover through controlled mechanisms of proliferation/ neogenesis and dampened β-cell death (Topp et al 2007). Numerous studies have shown that increased levels of free fatty acids and excessive glucose exposure (i.e.…”
Section: :2mentioning
confidence: 99%
“…The ZDF rat was developed by successive inbreeding of the most glucose intolerant ZF rats. The ZF rat remains normoglycaemic in the face of increasing obesity due to their ability to increase their β-cell mass and maintain a constant insulin secretory capacity despite a reduction in insulin sensitivity (Topp, et al 2007). These data indicate that β-cell proliferation and/or β-cell neogenesis from undifferentiated progenitor cells can occur if β-cell mass needs to be increased.…”
Section: Proteomic Studies Of Pancreas and Islets In Animal Models Ofmentioning
confidence: 99%